TRAINING FOR THE INNOVATIVE TEACHING AS A DETERMINANT OF THE PROFESSIONAL MOBILITY OF THE FUTURE TECHNOLOGY TEACHERS - Shevchenko, Liudmyla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the professional mobility and readiness for the innovative teaching of future technology teachers as interdependent components. The purpose of the article is to study the organizational and methodological aspects of forming the professional mobility of future technology teachers in the context of preparation for innovation activities at Ukrainian Teacher Training Universities. Using the complex of theoretical and empirical research methods, the main organizational and methodical aspects of training were determined: the construction of the individual trajectory of study based on selected disciplines; the acquisition of new branches of activity; the forming of the complete conception of technological education and future innovative teaching; the introduction of innovative technologies (interactive discussions, motivational trainings, group forms of work, a problem-solving training, design and research activities, mixed learning, etc.); implementation of Information and communications technology (ICT), distance, Smart and hybrid education systems (e-learning resources, electronic educational and methodical complexes, Web services, individual and group projects based on Web quests and Blog quests); the monitoring of the readiness level for professional mobility; the strengthening of the consultative and coordinating function of teachers. The implementation of certain aspects expands the possibilities of optimizing the educational process not only at the level of formation of the readiness for professional mobility, but also at the level of the entire system of training future technology teachers to innovative teaching. It requires: creating conditions for continuous learning; the orientation of the final stages of pedagogical education to the formation of students’ academic mobility; the rapid expansion of vertical and horizontal professional mobility ranges; the forming of future technology teachers’ readiness and the ability to change the specialization, the place of work and even the profession, if necessary, or to master several specialties or training profiles at the same time.